Cryptocurrency: more education, less hype - Weru, John (Technical Centre for Agricultural and Rural Cooperation, 2018)
John Weru is a Kenya-born writer, blogger and co-founder of PayHub East Africa. In a conversation with ICT Update, John talked about the rise of cryptocurrency, the potential of the blockchain to improve efficiency in the agricultural value chain in Africa, and theurgent need to educate people about the technology itself and the economy that it is creating.